2015
DOI: 10.1007/s11604-015-0416-3
|View full text |Cite
|
Sign up to set email alerts
|

Application of ultrasound elastography for determining carpal tunnel syndrome severity

Abstract: Sono-elastography could be a useful diagnostic method for evaluating CTS severity in affected cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 21 publications
1
34
0
Order By: Relevance
“…Ultrasound imaging is a beneficial and effective method for describing and analyzing the course of the brachial plexus and can guide therapeutic interventions . Sonoelastography is a sophisticated US technique that can detect tissue stiffness in vivo and can be helpful in the diagnosis of neuropathies . In this study, we showed that the brachial plexus in healthy individuals had intermediate stiffness with poor to moderate interobserver agreement and no correlation with age or sex.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Ultrasound imaging is a beneficial and effective method for describing and analyzing the course of the brachial plexus and can guide therapeutic interventions . Sonoelastography is a sophisticated US technique that can detect tissue stiffness in vivo and can be helpful in the diagnosis of neuropathies . In this study, we showed that the brachial plexus in healthy individuals had intermediate stiffness with poor to moderate interobserver agreement and no correlation with age or sex.…”
Section: Discussionmentioning
confidence: 59%
“…Due to the lack of any previous study evaluating brachial plexus elasticity, we could not compare our SWE and SE findings with the literature. There were a few studies on peripheral nerve elasticity, which were mostly about the median nerve in carpal tunnel syndrome (CTS) on either SWE or SE with different US machines . Kantarci et al compared the elastic modulus of the median nerve in patients with and without CTS on the longitudinal axis and found that the median nerve was stiffer in the CTS group (66.7 ± 26.5 kPa in the CTS group and 32.0 ± 8.4 kPa in the control group).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mean CSA, total blue pixels, and blue indexes were significantly different between cases with different degrees of severity and the controls. They concluded that sonoelastography could be used in the diagnosis and evaluation of the severity of CTS cases [24]. Kantarci et al have published a study utilizing quantitative shear wave elastography in which they concluded that median nerve stiffness was significantly increased in patients 57.1%, 72.3% and 58.5%, respectively, in the proximal and middle segments; 75%, 57.1%, 72.7% and 60% in the distal segments.…”
Section: Discussionmentioning
confidence: 99%